Ratings since the Asian crisis - Helmut Reisen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
The increased importance of rating agencies for emerging-market finance has brought their work to the attention of a wider group of observers - and under criticism. This paper evaluates whether the importance of ratings for developing-country finance has changed since the Asian Crisis and whether rating agencies have modified the determinants for their rating decisions. It also provides an analysis on recent suggestions by the Basel Committee on Banking Supervision, as these are very important for gauging the future role of sovereign ratings for foreign debt finance in developing countries. While the explanatory power of conventional rating determinants has declined since the Asian crisis, recent rating performance for Argentina and Turkey can still be qualified as lagging the markets, as variables of financial-sector strength and the endogenous effects of capital flows on macroeconomic variables seem to remain underemphasized in rating assessments. The market impact of sovereign ratings is predicted to decline as agencies have started to modify their country ceiling policy and as market participants try to exploit bond trading opportunities arising from the lagged nature of ratings. The paper presents theory and evidence to suggest that the Basel II Accord will destabilise private capital flows to the developing countries, if the current proposal to link regulatory bank capital to sovereign ratings is maintained: Assigning fixed minimum capital to bank assets whose risk weights are in turn determined by market-lagging cyclically determined ratings will reinforce the tendency of the capital ratio to work in a pro-cyclical way. – Asia ; financial crisis
Keywords: F3; 330; Länderrisiko; Asien; Finanzmarktkrise